Perspectives from Islamic Law on the Muhammadiyah Central Leadership's Tarjih Council and Its Significance for Religious Moderation - Umar, Marzuki; Sultan, Lomba; L, Sudirman; Ridwan, Muhammad Saleh; Syamsuddin, Darussalam; Idrus, Achmad Musyahid (Journal of Modern Islamic Studies and Civilization, 2024)
The research aims to explain and analyse the views of the Muhammadiyah central leadership assembly and its relevance to religious moderation. The method used in this research is a literature study that examines legal products produced by the Tarjih Council and in-depth interviews with Muhammadiyah's central and regional leaders regarding their views on religious moderation. This research shows that the Muhammadiyah central leadership tarjih council has provided moderate and flexible legal thinking. The legal products produced by the tarjih assembly have provided much knowledge to the public about how to act pretty, not easily blame others for differing opinions, be open to giving input, live side by side, be non-violent and prioritise the power of reason in looking at problems. This research concludes that the Muhammadiyah Tarjih Council's views align with the concept of moderation currently being developed by the Ministry of Religion.